(untitled) (Journal of Environmental Microbiology and Toxicology, 2023)
Toka is mostly produced from maize cob by the process of leaching, diluting decanting and removal of water residue. It is a commonly used food additive in northern Nigeria. Thirty-three Wistar rats were used to determine the acute and sub-acute toxicity of toka. The median lethal dose or LD50 of toka using the up and down procedure was discovered to be above 2000 mg/kg since administering 175 mg/kg, 500 mg/kg and 1000 mg/kg did not trigger death. However, during the 28-d study for sub-chronic toxicity study of Toka on the four test groups with graded doses of 0 mg/kg, 250 mg/kg, 500 mg/kg and 1000 g/kg. Physical behaviour such as redness of the eye started on the seventh day of the experiment while blisters on the mouth were observed from the fourteenth day of the experiment. There was no significant difference between the parameters and test groups. The findings of the current investigation revealed that there is not 54any significant difference in all the haematological parameters except haemoglobin. It also reveals various changes in the haematological parameters; White blood cell (RBC), packed cell volume (PCV), haemoglobin (HB), MCV, MCH, neutrophil (N) and Lymphocyte (L), did not show any significant difference with the control. Red blood cells (RBC) decreased significantly; this could be due to the increase in the breakdown of haemoglobin. There was an increase in the activity of ALT during the oral administration of Toka at different doses, this is an indication of the Liver malfunctioning. The outcome of this research indicated the toxicity of Toka on Wistar rats and therefore prolonged use of Toka as a food additive may have a toxic effect on some organs of the user.